Regional and Annual Variability in Subglacial Sediment Transport by Water for Two Glaciers in the Swiss Alps - Delaney, Ian; Bauder, Andreas; Werder, Mauro A.; Farinotti, Daniel (Frontiers in Earth Science, 2018)
Because the majority of sediment originates subglacially, as opposed to proglacially, focus must be given to subglacial sediment discharge. The latter, however is poorly constrained. We present a subglacial sediment transport time-series from two glacierized catchments (Gornergletscher and Aletschgletscher) in the Swiss Alps, based on hourly suspended sediment transport data and bedload transport estimates. This dataset is used to identify interannual and regional variability and to quantify the relationship between sediment transport and water discharge. Analysis of the relationship suggests that the access of water to subglacial sediment exerts substantial control on the quantity of sediment discharged. Historical data from Gornergletscher since the 1970's shows that elevated amounts of sediment were discharged in the 1980's, following the onset of increasing glacier melt. However, by 2016 and 2017, the sediment discharge returns to quantities below those in the 1970's, suggesting that sediment discharge can stabilize to new hydrological regimes over decadal timescales. Erosion rates for the two catchments (0.28 mm a^-1 to 0.49 mm a^-1) are smaller than in other glacierized catchments of the Swiss Alps ( 1 mm a^-1). In some cases they are even less than a third of those reported in earlier decades, highlighting substantial regional and interannual variability in catchment-scale erosion. Empirical models, calibrated with 2016–2017 data and relating water discharge to suspended sediment concentration, fail to capture the increase in sediment discharge over the 1980's. This suggests that processes secondary to runoff, such as changing access to subglacial sediment by meltwater, were responsible for the increase. Because subglacial sediment discharge depends on both water discharge and sediment availability, we argue that physically-based models are required to capture the evolution of subglacial sediment transport as glaciers retreat.